BENEFITS OF IMPLEMENTING STORY-BASED APPROACH IN IMPROVING YOUNG LEARNERS’ COGNITIVE SKILLS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article highlights benefits of using story-based approach in enhancing young learner’s language skills, as well as cognitive skills. Stories are fundamental when teaching young learners and the use of stories in the English classroom offers an effective way of introducing new language in a meaningful and memorable context. Moreover, they develop an understanding, respect and appreciation for other cultures, and can promote a positive attitude to people from different lands, races and religions